-2(0)+3y=-19

Simple and best practice solution for -2(0)+3y=-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(0)+3y=-19 equation:


Simplifying
-2(0) + 3y = -19

Multiply -2 * 0
0 + 3y = -19

Anything times zero is zero.
0 + 3y = -19
Remove the zero:
3y = -19

Solving
3y = -19

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '3'.
y = -6.333333333

Simplifying
y = -6.333333333

See similar equations:

| 8[8-k]=-2[k-5] | | 8=2q+-11 | | 7x-6=3(x+2)+10x | | D=Bak | | f(x)=2lx-1l+3 | | 5(x+8)=3x+9 | | .05a-3=0.3(2a-3) | | 9/4=45z | | 8/9x=4/9 | | 6(x-6)=-60 | | 2x-73=143-6x | | 80x-1000000=400000 | | 3+7x-2x+4=22 | | 18=s | | 7x^2+49x=-84 | | 7x+49x=-49 | | 3+7x-2x+4=2 | | x/-4=-177 | | 35/6x15/2 | | 0.8-2t=1-2t | | 5(0.3)= | | 4c+3c-5c= | | -8-5x^2=-29 | | 3xn+4=-6 | | 12n+5=21 | | 14.27x=114.50x | | 3Xn+4=-62 | | 7.5x=y | | 62-39= | | 2(c-3)=1.2-x | | X-(-4)=0 | | 14.27x=9.50x |

Equations solver categories